2009
DOI: 10.1073/pnas.0900419106
|View full text |Cite
|
Sign up to set email alerts
|

Mirroring of attention by neurons in macaque parietal cortex

Abstract: Macaques, like humans, rapidly orient their attention in the direction other individuals are looking. Both cortical and subcortical pathways have been proposed as neural mediators of social gaze following, but neither pathway has been characterized electrophysiologically in behaving animals. To address this gap, we recorded the activity of single neurons in the lateral intraparietal area (LIP) of rhesus macaques to determine whether and how this area might contribute to gaze following. A subset of LIP neurons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
111
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(123 citation statements)
references
References 78 publications
(106 reference statements)
9
111
0
Order By: Relevance
“…The properties of mirror neurons located in area LIP have been described by Shepherd and colleagues 97 . They found that a set of LIP neurons fired both when the monkey looked in the neuron-preferred direction and when it saw another monkey looking in the same direction.…”
Section: Box 1 | Mirror Neurons In Other Parietal Areasmentioning
confidence: 90%
“…The properties of mirror neurons located in area LIP have been described by Shepherd and colleagues 97 . They found that a set of LIP neurons fired both when the monkey looked in the neuron-preferred direction and when it saw another monkey looking in the same direction.…”
Section: Box 1 | Mirror Neurons In Other Parietal Areasmentioning
confidence: 90%
“…This work has revealed that, despite evidence for neural regions specialized for gaze processing, there has so far been little support for 'eye movement cells' with mirror properties. Recently, some support has emerged for the presence of mirror neurons in areas that control saccadic activity and overt attention such as the lateral intraparietal area (LIP; Shepherd, Klein, Deaner, & Platt, 2009), and the supplementary motor area including the supplementary eye fields (Mukamel et al, 2010). However, no evidence yet exists for neurons with mirror properties in areas that are specifically linked with eye movements such as the frontal eye fields.…”
Section: The Neural Basis Of Attention To Actionmentioning
confidence: 99%
“…However, no evidence yet exists for neurons with mirror properties in areas that are specifically linked with eye movements such as the frontal eye fields. Additionally, only Shepherd et al (2009) recorded mirror properties of cells specifically for observed and performed eye-movement behaviours. In contrast, mirror neurons which activate during the performance and observation of actions have been found throughout the premotor cortex (PMC), which is primarily responsible for planning a range of manual actions (CalvoMerino et al, 2005;Ferrari, Gallese, Rizzolatti, & Fogassi, 2003;.…”
Section: The Neural Basis Of Attention To Actionmentioning
confidence: 99%
“…Inactivation of neurons in the STS using a drug to block neuronal spiking impairs gaze-following in rhesus macaques, consistent with a role in identifying the locus of other animals' attention [102]. Shifting attention in response to the direction in which another individual is looking appears to be mediated by 'mirror' neurons in the lateral intraparietal area (LIP) that respond both when monkeys look in a particular direction and when they observe another monkey look in the same direction [103], another example of embodied cognition. Together, these findings suggest that a circuit connecting STS, amygdala and LIP subserves rapid, reflexive gaze-following in nonhuman primates.…”
Section: Cognitive and Neural Boundaries Of Cooperationmentioning
confidence: 99%